PENERAPAN MODEL PEMBELAJARAN INQUIRI UNTUK MENINGKATKAN HASIL BELAJAR PADA MATA PELAJARAN ILMU PENGETAHUAN ALAM - Sastra Wijaya (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2020)
Discussion of cycle I research results 1 meeting, from observations of the implementation of learning by using inquiry learning models in the first cycle of data. The first meeting obtained data that the observations on learning only reached 53.2, the results of observations on student activities 63, 87, and the level of mastery learning only reaching 24% with a class average value of 52. From observations of the implementation of learning by using inquiry learning models in the first cycle the second meeting obtained data that the observations on learning have experienced an increase, namely with the acquisition of 71.6, the results of observations on student activities 67.6, and the level of student mastery only reaches 48% with a class average value of 59.2. From observations in this second cycle of learning, learning using Inquiry learning models has been going well and smoothly because all students with experience capital in learning the first cycle of meetings II and II and the guidance from the teacher, the students have learned as well as possible and in the second cycle there were no students who were noisy themselves. From learning with the Inquiry learning model in the second cycle of data obtained, that student learning activities have increased with a percentage of 78.67%. With this data, it can be said that student learning activities have succeeded because they have achieved indicators of success. Then for student learning outcomes also increase, because the results of the evaluation given after learning is completed by telling students to work on the problems previously made by the teacher, respectively. each student gets good grades.